2011
DOI: 10.1017/s0007114511005551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of n-3 fatty acids on patients with advanced lung cancer: a double-blind, placebo-controlled study

Abstract: PUFA from fish oil appear to have anti-inflammatory and anti-oxidative effects and improve nutritional status in cancer patients. With this as background, the aim of the present study was to investigate the effect of EPA plus DHA on inflammatory condition, and oxidative and nutritional status in patients with lung cancer. In our multicentre, randomised, double-blind trial, thirty-three patients with a diagnosis of advanced inoperable non-small-cell lung cancer and undergoing chemotherapy were divided into two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 45 publications
7
73
0
9
Order By: Relevance
“…Moreover, it has also been proved that the continual consumption of EPA plus DHA significantly decreased the ROS levels in the plasma of patients with advanced inoperable non-small cell lung cancer (Finocchiaro et al, 2012). Consistent with this, similar findings were observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, it has also been proved that the continual consumption of EPA plus DHA significantly decreased the ROS levels in the plasma of patients with advanced inoperable non-small cell lung cancer (Finocchiaro et al, 2012). Consistent with this, similar findings were observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Baseline and post-treatment RBC PUFA levels in EMT study participants were similar to those reported previously in studies of omega-3 PUFA supplementation in healthy volunteers [13,19], women with breast hyperplasia [20][21] and in patients with lung cancer [22]. In particular, post-treatment % RBC EPA values were similar to those observed in an eight-week study of exactly the same EPA-FFA formulation and dose in healthy volunteers and inflammatory bowel disease patients [23].…”
Section: Discussionsupporting
confidence: 83%
“…There have been reports that inflammation and nutritional status improved by intervention with fish oil administration. (7,21,22). As fish oil is rich in EPA and DHA, we therefore considered that an improved CRP and decreased serum AA/EPA ratio, or n-6/n-3 ratio could be reached by eating a diet with n-3 fatty acid, such as EPA and DHA.…”
Section: Discussionmentioning
confidence: 99%